2020
DOI: 10.1128/jvi.01002-20
|View full text |Cite
|
Sign up to set email alerts
|

Filoviruses Use the HOPS Complex and UVRAG To Traffic to Niemann-Pick C1 Compartments during Viral Entry

Abstract: Ebola virus (EBOV) entry requires internalization into host cells and extensive trafficking through the endolysosomal network in order to reach late endosomal/lysosomal compartments that contain triggering factors for viral membrane fusion. These triggering factors include low-pH activated cellular cathepsin proteases, which cleave the EBOV glycoprotein (GP) to expose the binding domain of the filoviral receptor, Niemann-Pick C1 (NPC1). Here, we report that trafficking of EBOV to NPC1 requires expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To reach NPC1, filoviral particles must be internalized via macropinocytosis and then undergo extensive trafficking through the endosomal labyrinth whereby endosomes transition from Rab5+ to Rab7+ compartments [7][8][9]. Also involved in filovirus trafficking to NPC1 are the homotypic fusion and protein sorting (HOPS) and PIKfyve/ArPIKfyve/Sac3 (PAS) tethering and trafficking complexes [2,[10][11][12]. These complexes, along with the small GTPase Rab7, regulate vesicular fusion events required for specific trafficking of cargoes to late endosomes and lysosomes in cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To reach NPC1, filoviral particles must be internalized via macropinocytosis and then undergo extensive trafficking through the endosomal labyrinth whereby endosomes transition from Rab5+ to Rab7+ compartments [7][8][9]. Also involved in filovirus trafficking to NPC1 are the homotypic fusion and protein sorting (HOPS) and PIKfyve/ArPIKfyve/Sac3 (PAS) tethering and trafficking complexes [2,[10][11][12]. These complexes, along with the small GTPase Rab7, regulate vesicular fusion events required for specific trafficking of cargoes to late endosomes and lysosomes in cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the low pH environment of the endolysosome, the GP 1 subunit is cleaved by host low-pH-dependent cathepsins B and L, thereby releasing the mucin-like subdomains and glycan caps and exposing the receptor-binding site. Once exposed, the GP 1 receptor-binding site engages the NPC1 receptor, an intracellular cholesterol transporter that is ubiquitously expressed and located on the interior membrane of late endosomes and lysosomes [ 10 , 23 , 82 , 83 ]. Cleavage of the glycan cap was shown to induce changes in GP 1 , which in turn enabled flexibility in GP 2 , which is essential for fusion.…”
Section: Ebola Virus: From a Virology Point Of Viewmentioning
confidence: 99%
“…Many host proteins have been identified to be important for endosomal trafficking of EBOV, such as the small GTPase Rab7, the homotypic fusion and protein sorting (HOPS) complex, the UV Radiation Resistance Associated (UVRAG) protein, and the PIKfyve-ArPIKfyve-Sac3 trafficking complex (10,15,16). In addition, studies have shown that EBOV particles can stimulate signaling cascades such as the Akt/PI3K pathway, the latter being required for EBOV trafficking to NPC1 (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%